Conformationally Dependent Low-Frequency Motions of Proteins by Laser Raman Spectroscopy - Brown, K. G. (1972)
Low-frequency Raman bands (lower than 50 cm(-1)) exist in certain proteins. They are dependent upon the conformation of the protein molecule, but are relatively independent of the form of the sample, i.e., whether it is a film or a crystal. Low-frequency Raman spectra were obtained from samples of α-chymotrypsin that had been prepared in several ways. A peak at about 29 cm(-1) was found for all samples except the one that had been denatured with sodium dodecyl sulfate. Such low frequency motions must arise from vibrations that involve all, or very large portions, of the protein molecule.